Implementación de máquinas recicladoras para la generación de cultura de reciclaje por medio de música (2017)
The project's aim is to increase the recycling culture in Colombia by installing reverse vending machines in strategic sites throughout the cities in order for people to recycle their plastic bottles in these machines. For each bottle recycled, the machine will reward the client with a discount coupon that will act as an additional value added to the activity of recycling.